Comparative safety of bowel cleansers: protocol for a systematic review and network meta-analysis. Issue 6 (27th June 2018) - Barbeau, Pauline; Wolfe, Dianna; Yazdi, Fatemeh; Rice, Danielle B; Dube, Catherine; Kanji, Salmaan; Rostom, Alaa; Skidmore, Becky; Moher, David; Hutton, Brian
Abstract : Introduction: The US Food and Drug Administration has withdrawn the bowel cleansing kit HalfLytely (PEG 3500) with 10 mg bisacodyl tablets due to an increased risk of ischaemic colitis compared with the same kit with only 5 mg bisacodyl. This is of interest in Canada given that the bowel cleansing kit Bi-Peglyte (PEG 3500) with 15 mg bisacodyl is currently approved for use. The objective is to assess the comparative safety of various bowel cleansers with or without bisacodyl, with a primary interest inpolyethylene glycol (PEG)-based and sodium-picosulfate-based products. Methods and analysis: Given the existing volume of the literature, the review will be conducted in two stages. Stage 1 will consist of a scoping exercise by searching MEDLINE, Embase and the Cochrane Library (up to 21 November 2017) to identify randomised controlled trials, quasirandomised studies and non-randomised studies in which any bowel cleanser regimens were compared among persons undergoing colonoscopy. The outcomes will be mapped to establish a listing of the studies and their comparisons and outcomes currently available in the literature. From this, a data synthesis plan will be determined. In stage 2, a systematic review with meta-analyses will be pursued, focused on the bowel cleanser comparisons and outcomes of interest identified in stage 1. Two reviewers will screen, extract and quality assess the articles. Outcomes of interest include ischaemic colitis, electrolyte imbalances and their consequences, seizures, bowel perforation and patient tolerability. If sufficient data exist and studies are of sufficient homogeneity, network meta-analyses (NMAs) will be performed. Ethics and dissemination: Ethics approval was not necessary due to study design. Updating the safety profile of bowel cleansers among the generally healthy population undergoing colonoscopy is pertinent given recent approval changes. This will be the first NMA within this population. Policy considerations may be reconsidered to minimise risk during bowel cleanser use. PROSPERO registration number: CRD42018084720.